A survey on multivariate adaptive control charts: Recent developments and extensions. (7th August 2019) - Perdikis, Theodoros; Psarakis, Stelios
Abstract: In the world of business, quality improvement is of high importance for the manufacturing industries. Statistical process control via control charts provides an online monitoring of the product's characteristic. The adaptive feature is being widely used in the design parameters of a control chart, which allows at least one of them to change during the process monitoring. Specifically, a control chart is considered adaptive if at least one of the chart's parameters (sample size, sampling interval, or control limit coefficient) is allowed to change in real time on the basis of the actual values of the sample statistics. In this paper, recent developments in the design of multivariate adaptive control schemes are presented and discussed.